Diminished responses to monoaminergic antidepressants but not ketamine in a mouse model for neuropsychiatric lupus. (January 2019) - Srikumar, Bettadapura N; Naidu, Pattipati S; Kalidindi, Narasimharaju; Paschapur, Mahesh; Adepu, Bharath; Subramani, Siva; Nagar, Jignesh; Srivastava, Ratika; Sreedhara, Muppana V; Prasad, Durga Shiva; Das, Manish Lal; Louis, Justin V; et al.
Background: A significant proportion of patients suffering from major depression fail to remit following treatment and develop treatment-resistant depression. Developing novel treatments requires animal models with good predictive validity. MRL/lpr mice, an established model of systemic lupus erythematosus, show depression–like behavior. Aims: We evaluated responses to classical antidepressants, and associated immunological and biochemical changes in MRL/lpr mice. Methods and results: MRL/lpr mice showed increased immobility in the forced swim test, decreased wheel running and sucrose preference when compared with the controls, MRL/MpJ mice. In MRL/lpr mice, acute fluoxetine (30 mg/kg, intraperitoneally (i.p.)), imipramine (10 mg/kg, i.p.) or duloxetine (10 mg/kg, i.p.) did not decrease the immobility time in the Forced Swim Test. Interestingly, acute administration of combinations of olanzapine (0.03 mg/kg, subcutaneously)+fluoxetine (30 mg/kg, i.p.) or bupropion (10 mg/kg, i.p.)+fluoxetine (30 mg/kg, i.p.) retained efficacy. A single dose of ketamine but not three weeks of imipramine (10 mg/kg, i.p.) or escitalopram (5 mg/kg, i.p.) treatment in MRL/lpr mice restored sucrose preference. Further, we evaluated inflammatory, immune-mediated and neuronal mechanisms. In MRL/lpr mice, there was an increase in autoantibodies' titers, [3H]PK11195 binding and immune complex deposition. There was a significant infiltration of the brain by macrophages, neutrophils and T-lymphocytes. p11 mRNA expression was decreased in the prefrontal cortex. Further, there was an increase in the 5-HT2a R expression, plasma corticosterone and indoleamine 2, 3-dioxygenase activity. Conclusion: In summary, the MRL/lpr mice could be a useful model for Treatment Resistant Depression associated with immune dysfunction with potential to expedite antidepressant drug discovery.